2022
DOI: 10.1021/acsabm.2c00777
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Bioactive Scaffolds from ARX-g-(Zn@rGO)-HAp for Bone Tissue Engineering: In Vitro Antibacterial, Antitumor, and Biocompatibility Evaluations

Abstract: Advanced biomaterials are required with enhanced antibacterial and anticancer activities to obtain desirable biocompatibility during and after scaffold implantation in tissue engineering. Here, we report the development of a nanosystem by the hydrothermal method using different zinc (Zn) amounts and reduced graphene oxide (GO). Arabinoxylan, the nanosystem (Zn@rGO), and nanohydroxyapatite polymeric nanocomposites ARX-g-(Zn@rGO)/HAp were prepared by the free radical polymerization method, and porous bioactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In addition, these scaffolds’ sterility depends mainly on prolonged UV irradiation or autoclaving. At the same time, recent studies have shown that the antimicrobial properties of the scaffolds themselves can be improved by adding additional antimicrobial components such as Fe 3 O 4 [ 51 , 52 ], which will further enhance the application of SMP scaffolds in clinical tissue engineering if antimicrobial properties are obtained.…”
Section: Smps and Their Properties In Response To Different Stimulationsmentioning
confidence: 99%
“…In addition, these scaffolds’ sterility depends mainly on prolonged UV irradiation or autoclaving. At the same time, recent studies have shown that the antimicrobial properties of the scaffolds themselves can be improved by adding additional antimicrobial components such as Fe 3 O 4 [ 51 , 52 ], which will further enhance the application of SMP scaffolds in clinical tissue engineering if antimicrobial properties are obtained.…”
Section: Smps and Their Properties In Response To Different Stimulationsmentioning
confidence: 99%
“…Polymeric nanoparticles are a drug delivery system approach that utilizes polymers as carriers in the form of nanoparticles [ 20 , 21 , 22 ]. Polymeric nanoparticles are frequently produced from biopolymers such as chitosan in their formulation because they offer several advantages over other synthetic polymers, such as being green economy-friendly, eco-friendly, easy to make, bio-compatible, biodegradable, and low in their toxicity [ 23 , 24 ]. They have also been investigated for their ability to increase drug macromolecular permeation on epithelial membranes through the reversible opening of the transmembrane gap (tight junction) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HAP), the major biomineral of bones and teeth, stably exists in various parts of the human body, owing to its high stability and excellent biocompatibility. It is widely used in tissue repair, biomimetic materials, drugs/gene delivery, , electrochemical sensing, and so on. HAP has also been frequently applied for NA separation since Bernardi found its excellent discriminating capacity for single- and double-stranded DNA .…”
Section: Introductionmentioning
confidence: 99%